Exploring the Barriers to Effective Cooperative Learning Implementation in School Mathematics Classrooms - Mukuka, Angel; Mutarutinya, Vedaste; Balimuttajjo, Sudi (Problems of Education in the 21st Century, 2019)
Literature is replete with research confirming the benefits of cooperative learning on students’ academic achievement and attitude towards mathematics. Despite these benefits, cooperative learning implementation in most Zambian secondary school mathematics classrooms has remained a challenge. An explanatory sequential mixed methods research design was employed to determine the causes of teacher-resistance to cooperative learning implementation in selected schools. A cluster random sampling method was used to select 62 teachers (43 males and 19 female) of mathematics from six public secondary schools in Ndola district of Zambia. A questionnaire was administered to all the 62 teachers followed by lesson observations in six randomly selected grade 11 mathematics classrooms, whose teachers later attended a focus group discussion. Research findings revealed that the majority of participants prefer expository teaching to cooperative learning. More than 64% of the participants indicated that they resisted implementing cooperative learning in their classrooms due to shortcomings in; assessing learners, ensuring a disciplined class environment, completing the already bulky syllabus, handling large classes, students’ low reasoning abilities and preparation time versus high teaching loads. These results provide evidence on the need for more attention to how the identified challenges could be addressed not only in Zambian mathematics classrooms but in other educational settings elsewhere.
Keywords: Cooperative learning; Expository teaching; Mathematics classrooms; Mixed methods research